Peran Guru Penggerak dalam Program Komunitas Belajar (Kombel) untuk Mendukung Implementasi Kurikulum Merdeka di Satuan Pendidikan Kabupaten Brebes - Lutfi, M. Lutfi Baehaqi; Rinenggo, Rinenggo; Mindyasningrum, Mieke; Karim, Abdul (Jurnal Kridatama Sains dan Teknologi, 2024)
Educational problems often arise starting from the distribution of education, curriculum components, human resources which are considered lacking, the quality of educational services, facilities and infrastructure supporting learning, and so on. The driving teacher program is expected to become a motor in efforts to improve the quality of education. Driving teachers become icons of educational improvement, criticizing all existing problems and solving them by creating programs through learning communities in schools as a bridge for educators to solve learning problems. This research was conducted in education units in Brebes Regency, namely State Elementary School 01 Laren, Junior High School 01 Paguyangan, and Junior High School 02 Paguyangan. Researchers use Descriptive Qualitative research. The methods used in collecting data include interviews, observation and documentation. Data validity: Source triangulation and technique triangulation. The technique used in analyzing data is interactive analysis which includes data collection, data reduction, data presentation, conclusions